Information Dissemination through Embedded Financial Analysts: Evidence from China - Li, Zengquan; Wong, T. J.; Yu, Gwen (The Accounting Review, 2020)
ABSTRACT When emerging market firms disclose relationship-based transactions, they face a trade-off in which greater transparency may help lower their cost of capital at the cost of revealing proprietary information. We find that firms overcome this challenge by relying on analysts within their private networks (i.e., connected analysts) who, through repeated interaction with the firm, can better verify relationship-based transactions. Using Chinese firms, we show that firms with more connected analysts have more accurate consensus forecasts and lower forecast dispersion. When a connected analyst departs and stops covering a firm, the accuracy and informativeness of the unconnected analysts' forecasts decrease, suggesting that information spills over from the connected analyst to analysts outside the network. We find a potential mechanism for this information spillover: communication through common institutional clients, which suggests that embedded financial analysts—those sharing close connections with firms and analysts—serve as a channel for disseminating proprietary, hard-to-verify information. JEL Classifications: G14; G15; M40; N25. Data Availability: Data are available from sources identified in the text.